Worship and church building in small congregations : challenge and potential. An empirical-theological analysis of the practice of worship in correlation with church building in small free church congregations in Switzerland - Ott, Bernhard (University of Pretoria, 2025)
Thesis (PhD (PhD (Practical Theology))--University of Pretoria, 2024.